Cerebral amyloid angiopathy is associated with decreased functional brain connectivity - Drenth, Nadieh; van der Grond, Jeroen; Rombouts, Serge A.R.B.; van Buchem, Mark A.; Terwindt, Gisela M.; Wermer, Marieke J.H.; Chhatwal, Jasmeer P.; Gurol, M. Edip; Greenberg, Steven M.; van Rooden, Sanneke (NeuroImage clinical, 2021)
•Functional connectivity is diminished across the cortex in Dutch-type CAA.•Lower functional connectivity can already be found in presymptomatic CAA patients.•Decreased functional connectivity is most pronounced in symptomatic CAA patients. Cerebral amyloid angiopathy (CAA) is a major cause of intracerebral hemorrhage and neurological decline in the elderly. CAA results in focal brain lesions, but the influence on global brain functioning needs further investigation. Here we study functional brain connectivity in patients with Dutch type hereditary CAA using resting state functional MRI. Twenty-four DNA-proven Dutch CAA mutation carriers (11 presymptomatic, 13 symptomatic) and 29 age-matched control subjects were included. Using a set of standardized networks covering the entire cortex, we assessed both within- and between-network functional connectivity. We investigated group differences using general linear models corrected for age, sex and gray matter volume. First, all mutation carriers were contrasted against control subjects and subsequently presymptomatic- and symptomatic mutation carriers against control subjects separately, to assess in which stage of the disease differences could be found. All mutation carriers grouped together showed decreased connectivity in the medial and lateral visual networks, default mode network, executive control and bilateral frontoparietal networks. Symptomatic carriers showed diminished connectivity in all but one network, and between the left and right frontoparietal networks. Presymptomatic carriers also showed diminished connectivity, but only in the frontoparietal left network. In conclusion, global brain functioning is diminished in patients with CAA, predominantly in symptomatic CAA and can therefore be considered to be a late consequence of the disease.